Enhancing Critical Thinking Skills through Contextual Teaching and Learning - Saputri, Mitha Restu; Arni, Yusni; Lubis, Patricia H. M (Journal of Innovation and Research in Primary Education, 2025)
Critical thinking skills are essential for elementary students' academic success and twenty-first-century workforce preparation. However, many Indonesian elementary schools still employ teacher-centered approaches that limit students' active engagement and critical thinking development. This study aimed to determine the effect of the Contextual Teaching and Learning (CTL) model on critical thinking skills of fourth-grade students at SDN Sumber Agung. A quasi-experimental design with Nonequivalent Control Group Design was employed, involving 56 fourth-grade students selected through simple random sampling. The experimental group (n=28) received CTL instruction, while the control group (n=28) was taught using conventional teacher-centered methods. Critical thinking skills were assessed using a validated 15-item multiple-choice test based on six indicators: focus, reason, inference, situation, clarify, and overview. The instrument demonstrated good reliability (Cronbach's alpha = 0.756). Data were analyzed using Independent Sample T-Test after verifying normality and homogeneity assumptions. N-Gain analysis was conducted to determine practical effectiveness. The Independent Sample T-Test revealed significant differences between groups (t = 3.752, p < 0.001), with the experimental group achieving higher posttest scores (M = 81.92) compared to the control group (M = 69.81). N-Gain analysis showed the experimental group attained moderately effective improvement (63.11%) while the control group showed ineffective gains (32.23%). The CTL model significantly enhances students' critical thinking skills compared to conventional teaching methods. These findings validate constructivist learning theory and provide empirical evidence for implementing contextualized approaches in Indonesian elementary education to develop essential critical thinking capabilities.